Cost-effectiveness analysis of pharmacogenetic-guided warfarin dosing in Thailand - Chong,H. (Elsevier Limited, 2015)
© 2014 Elsevier Ltd. All rights reserved. Introduction Pharmacogenetic (PGx) test is a useful tool for guiding physician on an initiation of an optimal warfarin dose. To implement of such strategy, the evidence on the economic value is needed. This study aimed to determine the cost-effectiveness of PGx-guided warfarin dosing compared with usual care (UC). Methods A decision analytic model was used to compare projected lifetime costs and quality-adjusted life years (QALYs) accrued to warfarin users through PGx or UC for a hypothetical cohort of 1,000 patients. The model was populated with relevant information from systematic review, and electronic hospital-database. Incremental cost-effectiveness ratios (ICERs) were calculated based on healthcare system and societal perspectives. All costs were presented at year 2013. A series of sensitivity analyses were performed to determine the robustness of the findings. Results From healthcare system perspective, PGx increases QALY by 0.002 and cost by 2,959 THB (99 USD) compared with UC. Thus, the ICER is 1,477,042 THB (49,234 USD) per QALY gained. From societal perspective, PGx results in 0.002 QALY gained, and increases costs by 2,953 THB (98 USD) compared with UC (ICER 1,473,852 THB [49,128 USD] per QALY gained). Results are sensitive to the risk ratio (RR) of major bleeding in VKORC1 variant, the efficacy of PGx-guided dosing, and the cost of PGx test. Conclusion Our finding suggests that PGx-guided warfarin dosing is unlikely to be a cost-effective intervention in Thailand. This evidence assists policy makers and clinicians in efficiently allocating scarce resources.